Induced Genetic Variations in Stomatal Density and Size of Rice Strongly Affects Water Use Efficiency and Responses to Drought Stresses - Pitaloka, Mutiara K.; Caine, Robert S.; Hepworth, Christopher; Harrison, Emily L.; Sloan, Jennifer; Chutteang, Cattleya; Phunthong, Chutima; Nongngok, Rangsan; Toojinda, Theerayut; Ruengphayak, Siriphat; Arikit, Siwaret; Gray, Julie E.; et al. (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) is an important food crop relied upon by billions of people worldwide. However, with increasing pressure from climate change and rapid population growth, cultivation is very water- intensive. Therefore, it is critical to produce rice that is high-yielding and genetically more water-use efficient . Here, using the stabilized fast- neutron mutagenized population of Jao Hom Nin (JHN) - a popular purple rice cultivar - we microscopically examined hundreds of flag leaves to identify four stomatal model mutants with either high density (HD) or low density (LD) stomata,and small-sized (SS) or big-sized (BS) stomata. With similar genetic background and uniformity, the stomatal model mutants were used to understand the role of stomatal variants on physiological responses to abiotic stress. Our results show that SS and HD respond better to increasing CO2 concentration and HD has higher stomatal conductance (gs) compared to the other stomatal model mutants, although the effects on gas exchange or overall plant performance were small under greenhouse conditions. In addition, the results of our drought experiments suggest that LD and SS can better adapt to restricted water conditions, and LD showed higher water use efficiency (WUE) and biomass/plant than other stomatal model mutants under long-term restricted water treatment. Finally, our study suggests that reducing stomata density and size may play a promising role for further work on developing a climate-ready rice variety to adapt to drought and heat stress. We propose that low stomata density and small size have high potential as genetic donors for improving WUE in climate-ready rice.